Adolescence and philosophy (Journal of Parents and Teachers, 2014)
Teenagers try to deal with a lot of concerns and enigmas related to their past, present and future lives. Adolescents have the philosophy inside and it’s their parents and educators duty to stimulate the questions and guide the answers. They have a questioning attitude towards the established systems, a philosophic activity to think about the world around them from different points of view and to invent new concepts to deal with radical new things.
Keywords: adolescence; philosophy; psychology; relationships; sexual education; sexuality.